Endomyocardial biopsy safety and clinical yield in pediatric myocarditis: An Italian perspective. Issue 4 (29th October 2015) - Brighenti, Maurizio; Donti, Andrea; Giulia Gagliardi, Maria; Maschietto, Nicola; Marini, Davide; Lombardi, Maristella; Vairo, Ugo; Agnoletti, Gabriella; Milanesi, Ornella; Pongiglione, Giacomo; Bonvicini, Marco; ,
Abstract : Objectives: The objective of this investigation is to evaluate the safety, the impact of endomyocardial biopsy (EMB) results in myocarditis management and the incidence of different etiologies of myocarditis in a pediatric population. Background: Although EMB is an established diagnostic tool to evaluate suspected myocarditis, there is lack of clear diagnostic and management guidelines for myocarditis in pediatric patients, particularly in infants. Methods: We performed a retrospective database review and subsequent outcomes analysis from five Italian pediatric cardiology centers to identify patients aged 0–18 years who underwent EMB for suspected myocarditis or inflammatory cardiomyopathy (ICMP) between 2009 and 2011. Results: EMB was performed in 41 children, of which 16 were male. The population ranged between 16 days of age to 17 years (mean age at EMB = 5.2 ± 4.9 years). The overall incidence of EMB‐related complications was 15.5% (31.2% in infants, and 6.8% in children > 1 year of age; P  = 0.079) while the incidence of EMB‐driven treatment changes was 29.2%. Histological examination together with PCR on heart biopsy specimens allowed an etiological diagnosis in 26/41 patients (63%). Among the 15 patients (36.5%) with diagnosis of dilated cardiomyopathy (DCM) 11 had idiopathic DCM. Finally, we found an overall incidence of death/cardiac transplantation of 24%. Conclusions: In a pediatric population with suspected myocarditis/ICMP, EMB was useful in confirming the diagnosis only in 41% of cases but showed an overall diagnostic power of 63%. As complications of EBM are not negligible, particularly in infants, the risk/benefit ratio should be taken into account in each patient. © 2015 Wiley Periodicals, Inc.